A Not-So-Radical Approach to Human Rights in Islam - Ibrahim, Abadir M. (The journal of religion, 2016)
The article explores the challenges in ethico-legal perspectives on Islamic normative system dealing with societal problems of Islamic texts, Islamic heritage and Muslims daily life. It asserts the levels of the discourse system in order to provide a social approach in human rights in Islam such as the basic foundational values and objectives of the Islamic ethics and law. It also discusses the importance of understanding the foundational values of Qur'an and Islam.